2020
DOI: 10.1002/alz.12236
|View full text |Cite
|
Sign up to set email alerts
|

Head‐to‐head comparison of clinical performance of CSF phospho‐tau T181 and T217 biomarkers for Alzheimer's disease diagnosis

Abstract: Introduction Phosphorylated tau (p‐tau) in cerebrospinal fluid (CSF) is an established Alzheimer's disease (AD) biomarker. Novel immunoassays targeting N‐terminal and mid‐region p‐tau181 and p‐tau217 fragments are available, but head‐to‐head comparison in clinical settings is lacking. Methods N‐terminal‐directed p‐tau217 (N‐p‐tau217), N‐terminal‐directed p‐tau181 (N‐p‐tau181), and standard mid‐region p‐tau181 (Mid‐p‐tau181) biomarkers in CSF were evaluated in three cohorts (n = 503) to assess diagnostic perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
105
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(110 citation statements)
references
References 56 publications
5
105
0
Order By: Relevance
“…To date, there have been twelve independent data reports on plasma p-tau181 and two on plasma p-tau217. Yet, the limited evidence available may suggest some superiority of plasma p-tau217 over plasma p-tau181 [82], which is in line with CSF comparisons of the same biomarkers [92,93,117]. However, a biomarker comparison using the same detector antibody in sandwich immunoassay format has yet to be performed, and therefore it cannot be determined if the observed superiority is either assay or epitope dependent.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…To date, there have been twelve independent data reports on plasma p-tau181 and two on plasma p-tau217. Yet, the limited evidence available may suggest some superiority of plasma p-tau217 over plasma p-tau181 [82], which is in line with CSF comparisons of the same biomarkers [92,93,117]. However, a biomarker comparison using the same detector antibody in sandwich immunoassay format has yet to be performed, and therefore it cannot be determined if the observed superiority is either assay or epitope dependent.…”
Section: Discussionmentioning
confidence: 96%
“…Tatebe et al [76] developed a p-tau181 assay by substituting the detection antibody in the Simoa™ Tau 2.0 total tau kit for a p-tau181-specific monoclonal antibody. Karikari et al [79,93] developed novel p-tau181 and p-tau217 assays targeting p-tau forms that also contain the N-terminal amino acid 6-18 epitope. Similarly, the Eli Lilly-developed p-tau181 and p-tau217 are located N-terminally to the p-tau sites [56].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The loss of normal functions and the gain of toxic functions of Tau have been linked with the pathogenesis of AD [2][3][4][5][6][7]. Mounting evidence has suggested that the cerebrospinal fluid (CSF) levels of tau and phosphorylated tau are linearly associated with symptom severity of AD [8][9][10][11], suggesting tau as a promising biomarker for early diagnosis and prognostic prediction. However, clinical application of CSF biomarkers has been hindered by high cost, invasiveness, and side effects of lumbar punctures, such as positional headache [12].…”
Section: Introductionmentioning
confidence: 99%